2018
DOI: 10.15296/ijwhr.2019.48
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Decision to Have Child Among Iranian Couples; An Online Survey

Abstract: Objectives: Total fertility rate (TFR) in Iran is declining to the lowest low level over the past 30 years. In order to increase the TFR, the influencing factors for willingness to have child should be identified. The aim of this study was to identify the factors that influence the willingness of Iranian men and women to have child. Materials and Methods: This cross-sectional study was conducted on married Iranian men and women through an online survey. A questionnaire consisting of demographic characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Evidence shows that fertility rate is under replacement in Iran (1.5 children per woman during reproductive age; Hosseini et al, 2021 ). A recent study in Iran showed that those participants with a higher age-gap with their husbands and with having more children had more negative attitudes toward fertility, and those who had husbands with higher level of education, and higher score of social and emotional factors were more positive toward fertility ( Jafarzadeh Esfehani et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that fertility rate is under replacement in Iran (1.5 children per woman during reproductive age; Hosseini et al, 2021 ). A recent study in Iran showed that those participants with a higher age-gap with their husbands and with having more children had more negative attitudes toward fertility, and those who had husbands with higher level of education, and higher score of social and emotional factors were more positive toward fertility ( Jafarzadeh Esfehani et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, only one utilized the Poisson model without assessing dispersion. These investigations revealed significant effects on NLC from variables such as the mother's age, income, maternal and paternal education, ethnicity, place of residence, women's employment, the NCEX, the number of pregnancies, and the DHCH (3,7,16,25). Nonetheless, a study encompassing five developed countries (Japan, South Korea, the United States, France, and Sweden) demonstrated that the MAM and DHCH significantly influenced NLC (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%